Optimization of the Liquid Scintillator Composition - Batyrkhanov, А.; Beznosko, Dmitriy; Yelshibekov, K.; Iakovlev, A. (38th International Conference on High Energy Physics, 2016)
Nowadays, many particle detectors use liquid scintillator (LS) as a detection medium. In particular, Water-based Liquid Scintillator (WbLS) that is a new material currently under development. It is based on the idea of dissolving the organic scintillator in water using special surfactants. This material strives to achieve the novel detection techniques by combining the Cherenkov and scintillation light, as well as the total cost reduction compared to pure liquid scintillator. An important part of either the pure LS or WbLS production is to choose the right fluor and shifter and their concentrations. The choice affects the spectral distribution of the light output and the detection efficiency as each photodetector has its own spectral sensitivity region. This work presents the results of the study on the pseudocumen (PC) based LS with the PPO and POPOP/MSB as a fluor and shifters of choice. Both the total light yield and the spectral differences in the outputs with different amounts of components are shown. This study can be applied to plastic scintillators as well. 38th